2017
DOI: 10.1159/000479699
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and Environmental Enrichment Differentially Affect Neurogenesis, Dendritic Spine Immunolabeling and Synaptogenesis in the Hippocampus of Young and Reproductively Senescent Female Rats

Abstract: Background: Studies examining the ability of estrogen replacement therapy (ERT) to enhance memory in women, and in animal models, have not produced consistent results. However, studies examining the effects of activity and exposure to novel environments consistently find enhancement of memory. Methods: An animal model of reproductive aging was used to determine if estradiol (E2) replacement, activity, and/or exposure to an enriched environment could act synergistically to improve memory, and neural correlates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…The actions of steroids in the brain are complex and depend of many factors such as the strain, the species, the timing, the concentration, and the rhythm of secretion, as well as the regions studied (Duarte-Guterman et al, 2015 ; Heberden, 2017 ). Sex steroids are well-documented for impacting neuronal plasticity including synaptogenesis/spinogenesis such as shown for estrogens (Fester et al, 2012 ; Brandt et al, 2013 ; Sellers et al, 2015 ; Sager et al, 2017 ), progesterone (Sakamoto et al, 2001b , 2002 ; Zhao et al, 2011 ), and testosterone (Manolides and Baloyannis, 1984 ; Devoogd et al, 1985 ). They have been also well-characterized for their role on learning/memory processes (Frye and Walf, 2008 , 2010 ; Frye et al, 2008 ; Phan et al, 2012 ; Celec et al, 2015 ; Frick et al, 2015 ).…”
Section: Role Of Steroids In the Brains Of Fish Mammals And Birdsmentioning
confidence: 99%
“…The actions of steroids in the brain are complex and depend of many factors such as the strain, the species, the timing, the concentration, and the rhythm of secretion, as well as the regions studied (Duarte-Guterman et al, 2015 ; Heberden, 2017 ). Sex steroids are well-documented for impacting neuronal plasticity including synaptogenesis/spinogenesis such as shown for estrogens (Fester et al, 2012 ; Brandt et al, 2013 ; Sellers et al, 2015 ; Sager et al, 2017 ), progesterone (Sakamoto et al, 2001b , 2002 ; Zhao et al, 2011 ), and testosterone (Manolides and Baloyannis, 1984 ; Devoogd et al, 1985 ). They have been also well-characterized for their role on learning/memory processes (Frye and Walf, 2008 , 2010 ; Frye et al, 2008 ; Phan et al, 2012 ; Celec et al, 2015 ; Frick et al, 2015 ).…”
Section: Role Of Steroids In the Brains Of Fish Mammals And Birdsmentioning
confidence: 99%
“…However, a wealth of data also points out complex actions in the brain of vertebrates during development and in adulthood (Duarte-Guterman et al, 2015b;Heberden, 2017). Many experimental results highlighted the effects of estradiol (E2) and progesterone (P4) on neuronal plasticity through different processes such as synaptogenesis (Fester et al, 2012;Sager et al, 2017;Sakamoto et al, 2001Sakamoto et al, , 2001) stem cell proliferation or differentiation, migration, and neuron survival (Azcoitia et al, 2001;Brinton et al, 2008;Brock et al, 2010;Diotel et al, 2018;Mazzucco et al, 2006;Murashov et al, 2004;Tsutsui, 2008;Wang et al, 2003;Zhang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A study testing the effects of exercise on skeletal muscles, demonstrated that exercise training improves mitochondrial function oxidative capacities in both male and female rats, but it is more pronounced in males (Farhat et al, 2017). In the case of female rats, the effectiveness of regular and moderate intensity physical exercise is age-dependent (Marosi et al, 2012) and RS female may require extended period of physical activity before the benefits on memory become apparent (Sager et al, 2018), which indicates that it is important to consider titration of exercise for female animals.…”
Section: Discussionmentioning
confidence: 99%